Resgate da obra do engenheiro civil Eladio Dieste na cidade de Artigas, Uruguai - Fagúndez, Gilberto Pilecco (2016)
This Master’s thesis evokes the resurgence of design work by Uruguayan Civil Engineer Eladio Dieste in Artigas, Uruguay, with a focus on residential architecture inherited by the city, as a strategy to display and preserve the architectural heritage comprising an innovative building technique: the reinforced brickwork domes. During this research, a study of modern Uruguayan architecture was undertaken to establish chronologically the period in which Eladios’ designs were built. In conjunction with this, the engineer’s personal life was also analysed in order to understand his personal, educational, ideological and professional background and how these helped form his professional approach and lead him towards the creation of reinforced brickwork, which is renowned and studied worldwide equally for horizontal and vertical planes, slopes and curves, gausa vaults or self-supporting, pleated walls, controlled surfaces or for towers and reservoirs. With brick being the main material used and with the effect of natural light and curves, thin shells were created capable of withstanding large spans without the need for mid-span support, creating a mesmerising play of light and shadow. The research adopted the bibliography study method, site visits, event attendance and analysis of plans and briefs, directing the study to form an exclusive and firsthand inventory of the residential designs by Eladio Dieste in the city of Artigas. In the case study structural, formal, programme and conceptual characteristics for Saul Dieste House (1955) and Dr Gomes Gotuzzo House (1967) were analysed. As a final research result, an exclusive inventory was formed concerning the residential designs in Eladio Dieste’s hometown.